Unknown but not unloved - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Tamarind By HPM Gunasena & A Hughes, ICUC, UK, 2000. 171 pp. ISBN 0854327274 GBP 15 Euro 24.70 Free for orders from ACP countries